An automated inverse method for slug tests—over-damped case—in confined aquifers - Rozos, Evangelos; Akylas, Evangelos; Koussis, Antonis D. (My University, 2015)
Abstract: Slug tests offer an efficient method for estimating the hydraulic parameters of an aquifer without water pumping. Two inverse methods are typically used to assess the slug test data and derive parameter estimates of a confined aquifer. The first method provides estimates of both hydraulic conductivity and specific storage, is visual (hence difficult to automate), and is based on the transient-flow analytical solution of Cooper et al. The second method, proposed by Hvorslev, is very straightforward, but provides only hydraulic conductivity estimates. In this study, we are testing the recently proposed quasi-steady method of Koussis and Akylas, which enables the estimation of both hydraulic parameters and, furthermore, can be easily implemented in computer code or an electronic spreadsheet. This quasi-steady method was coupled with the shuffled complex evolution optimization method to fully automate parameter estimation. This coupling is tested using data from field observations, synthetic data produced from the transient-flow analytical solution, and synthetic data with noise. The results show the usefulness and the limitations of the proposed method.
Keywords: Confined aquifers; Optimization; Parameters estimation; SCE method; Slug test